2011
DOI: 10.1245/s10434-011-1768-2
|View full text |Cite
|
Sign up to set email alerts
|

Borrmann’s Macroscopic Criteria and p-Smad2 Expression Are Useful Predictive Prognostic Markers for Cytology-Positive Gastric Cancer Patients Without Overt Peritoneal Metastasis

Abstract: Activated Smad signaling might be associated with a high potential for peritoneal recurrence in CY1P0 patients. Borrmann's macroscopic criteria and p-Smad2 expression are useful markers for surgeons selecting advanced gastric cancer patients with CY1P0 for gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Poor prognostic factors should also be considered in patients with CY1 gastric cancer. It has been reported that patients with a high rate of lymph node metastasis or type 4 CY1 gastric cancer have a poor outlook [9][10][11]. It may be difficult to devise an appropriate treatment strategy for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognostic factors should also be considered in patients with CY1 gastric cancer. It has been reported that patients with a high rate of lymph node metastasis or type 4 CY1 gastric cancer have a poor outlook [9][10][11]. It may be difficult to devise an appropriate treatment strategy for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Type 4 tumors were also reported to have an extremely poor prognosis compared to non-Type 4 tumors [20,21]. Kano et al [22] found by a multivariate analysis that Type 4 tumor, R2 resection, lymph node metastasis, and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the risk factors for developing metachronous peritoneal carcinomatosis are advanced stage at diagnosis, right-side cancer location, infiltrative or ulcero-infiltrative carcinomas, and history of perforation and obstruction in colorectal cancer (4)(5)(6)(7), but these factors are not reliable predictors for peritoneal metastasis in individuals. Although many researchers have investigated the mechanism of peritoneal dissemination in terms of genetic variations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), common changes of gene expression in tumor progression to peritoneal metastasis have not yet been clarified.…”
mentioning
confidence: 99%